Anatomical and Palynological Characters of Celtis L. In Kurdistan-Iraq - Shahbaz, Saleem E.; Sharif, Nazar M. (Science Journal of University of Zakho, 2017)
Anatomical and palynological characters of Celtis genus growing in Iraq were studied in an attempt to provide useful features to delimit taxa and to refine taxonomic relationships. Results revealed the presence of lithocysts inside the leaf structure of C. tournefortii with few of them forming very small protrusion out of the leaf, while in C. australis lithocysts form large protrusion out from the leaf. The large midrib adaxial hump of C. tournefortii constitute a wide area between the two sides of the leaf blade, while in C. australis the small midrib adaxial hump produce narrow area between the two sides of the leaf blade. Stomata are of anomocytic type in C. australis while, anomocytic and paracytic in C. tourneforti. Furthermore, simple hairs are dense on the adaxial side of the petiole of C. tournefortii var. tournefortii, while absent from the adaxial side of the petiole of C. tournefortii var. glabrata. Leaves of all taxa are distinctly bifacial, hypostomatic, and provided with one layer of palisade parenchyma. Pollen grains are 3-porate, rarely 4-porate. A sunken area in the aperture surrounding a pore is distinct. Pollen is mediae in size and subprolate in shape, the pollen grains of C. australis together with var. glabrata belong to Celtis-type grain, while, var. tournefoertii to the Ulmus-type grain. The high anatomical and palynological differences between varieties of C. tournefoertii support promotion of these two varieties to the specific level.